Prospective Clinical Trial of Corneal Reconstruction With Biomaterial-Free Cultured Oral Mucosal Epithelial Cell Sheets. Issue 1 (January 2018) - Kim, Yu Jeong; Lee, Hyun Ju; Ryu, Jin Suk; Kim, Yun Hee; Jeon, Saewha; Oh, Joo Youn; Choung, Ho Kyung; Khwarg, Sang In; Wee, Won Ryang; Kim, Mee Kum
Abstract : Purpose: To investigate the efficacy and safety of transplantation with biomaterial-free cultured oral mucosal epithelial cell sheets (COMECs) for ocular reconstruction in subjects with total limbal stem cell deficiency. Methods: A prospective clinical trial (NCT02149732) was conducted in 8 subjects with total limbal stem cell deficiency after approval from the institutional review board of Seoul National University Hospital (H-0707-043-213) and the Ministry of Food and Drug Safety of Korea. COMECs were prepared in a culture system without the use of any temperature-sensitive polymers or carriers. The COMECs were transplanted without suture fixation. Four subjects underwent penetrating keratoplasty after stabilization of the COMEC transplant. Stable epithelialization, changes in visual acuity, and postoperative complications were evaluated for 6 months. Corneal cytokeratins (K) of 4 subjects who underwent penetrating keratoplasty were stained with an immunofluorescent agent. Results: The ocular surface was successfully reconstructed in 6 eyes. Complete stable epithelialization was achieved within a mean of 53.6 days. Visual improvement (≥2 lines) was achieved in 62.5% of the eyes. K12 (corneal phenotype), K4, and K13 (mucosal phenotype) were well expressed in grafts after keratoplasty, whereas K1, K8, and K19 were barely expressed. No ocular infections, local tumor formation, or remarkable systemic complications were observed. Ocular reconstruction using COMECs failed in 2 eyes, which had full symblepharon in 4 quadrants. Conclusions: Transplanting biomaterial-free COMECs seems to be an efficient and safe procedure to reconstruct the ocular surface in patients who are completely limbal stem cell deficient without a full symblepharon. Abstract : Supplemental Digital Content is Available in the Text.